2014
DOI: 10.15625/0866-7160/v30n1.5410
|View full text |Cite
|
Sign up to set email alerts
|

Gyrocheilos W. T. Wang (Gesneriaceae) a new genus for the flora of Vietnam

Abstract: T¹p chÝ Sinh häc 3-2008 bae sung chi gyrocheilos W. T. Wang (hä Tai voi-Gesneriaceae) cho hÖ thùc vËt viÖt nam Vò Xu©n Ph−¬ng

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…10 Because of its high impact strength, elevated tensile strength, good chemical resistance, low density, and also rather low cost, polypropylene (PP) is one of the most widely used thermoplastics. 11 It is widely applied in the production of fibers, films for food packaging, bottles, and tubes. It has been demonstrated that the introduction of relatively small amounts of inorganic nanostructured materials in PP can effectively improve its chemical and mechanical stability.…”
Section: Introductionmentioning
confidence: 99%
“…10 Because of its high impact strength, elevated tensile strength, good chemical resistance, low density, and also rather low cost, polypropylene (PP) is one of the most widely used thermoplastics. 11 It is widely applied in the production of fibers, films for food packaging, bottles, and tubes. It has been demonstrated that the introduction of relatively small amounts of inorganic nanostructured materials in PP can effectively improve its chemical and mechanical stability.…”
Section: Introductionmentioning
confidence: 99%